Nietzsche en 90 minutos - Strathern, Paul, 1940-; Padilla Villate, José Antonio; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2014)
Reading for those who wish to push further; and chronologies that place Nietzsche within his own age and in the broader scheme of philosophy.
Online resource; title from ePub title page (Digitalia, viewed June 28, 2017)
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Philosophers -- Germany -- Biography; Electronic books